Sputum TNF markers are increased in neutrophilic and severe asthma and are reduced by azithromycin treatment. Issue 7 (2nd March 2021) - Niessen, Natalie M.; Gibson, Peter G.; Baines, Katherine J.; Barker, Daniel; Yang, Ian A.; Upham, John W.; Reynolds, Paul N.; Hodge, Sandra; James, Alan L.; Jenkins, Christine; Peters, Matthew J.; Marks, Guy B.; et al.
Abstract: Background: The AMAZES randomized controlled trial demonstrated that long‐term low‐dose azithromycin treatment reduces exacerbations of poorly controlled asthma, but the therapeutic mechanisms remain unclear. Dysregulation of the inflammatory tumour necrosis factor (TNF) pathway is implicated in asthma and could be suppressed by azithromycin. We aimed to determine the inflammatory and clinical associations of soluble TNF signalling proteins (TNF receptors [TNFR] 1 and 2, TNF) in sputum and serum, and to test the effect of 48 weeks of azithromycin vs placebo on TNF markers. Methods: Sputum supernatant and serum TNFR1, TNFR2 (n = 142; 75 azithromycin‐treated, 67 placebo‐treated) and TNF (n = 48; 22 azithromycin‐treated, 26 placebo‐treated) were measured by ELISA in an AMAZES trial sub‐population at baseline and end of treatment. Baseline levels were compared between sputum inflammatory phenotypes, severe/non‐severe asthma and frequent/non‐frequent exacerbators. Effect of azithromycin on markers was tested using linear mixed models. Results: Baseline sputum TNFR1 and TNFR2 were significantly increased in neutrophilic vs non‐neutrophilic asthma phenotypes, while serum markers did not differ. Sputum TNFR1 and TNFR2 were increased in severe asthma and correlated with poorer lung function, worse asthma control and increasing age. Serum TNFR1 was also increased in severe asthma. Sputum and serum TNFR2 were increased in frequent exacerbators. Azithromycin treatment significantly reduced sputum TNFR2 and TNF relative to placebo, specifically in non‐eosinophilic participants. Conclusions: We demonstrate dysregulation of TNF markers, particularly in the airways, that relates to clinically important phenotypes of asthma including neutrophilic and severe asthma. Suppression of dysregulated TNF signalling by azithromycin could contribute to its therapeutic mechanism. Abstract : Increased sputum and serum TNF markers are associated with neutrophilic asthma, severe asthma and frequent exacerbation history. Azithromycin treatment reduces airway and systemic TNF markers, suggesting an anti‐inflammatory mechanism. Azithromycin effect on TNF markers is most pronounced in non‐eosinophilic asthma. Effect on serum but not sputum markers is related to sputum bacteria‐positive culture, linking antibiotic effect to modulation of systemic inflammation. Abbreviations: AMAZES‐RCT, Asthma and Macrolides: The Azithromycin Efficacy and Safety study—Randomized Control Trial; TNF, tumor necrosis factor; TNFR, TNF receptor.